A dynamic probabilistic route discovery for mobile ad hoc networks. (2nd December 2009) - Abdulai, Jamal-Deen; Ould-Khaoua, Mohamed; Mackenzie, Lewis M.; Mohammed, Aminu
Blind flooding has been extensively used in ad hoc routing protocols for on-demand route discovery, where a mobile node blindly rebroadcasts received route request (RREQ) packets until a route to a particular destination is established. This can potentially lead to high channel contention, causing redundant retransmissions and thus, excessive packet collisions in the network. Such a phenomenon induces what is known as the broadcast storm problem, which has been shown to greatly increase the network communication overhead and end-to-end delay. In this paper, we show that the deleterious impact of such a problem can be considerably reduced if measures are taken during the dissemination of RREQ packets. We propose a generic probabilistic method for route discovery that dynamically computes the forwarding probability at a given node and can significantly reduce the overhead associated with the dissemination of RREQs. Our analysis reveals that equipping a routing protocol with the proposed probabilistic route discovery can result in a significant reduction of routing control overhead while achieving good throughput.